Grenada : Disaster Resilience Strategy. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2022)
Natural disasters and climate change are existential threats to Grenada, with annual losses from these events estimated at 1.7 percent of GDP. Grenada has proactively pursued resilience-building, with its Climate Change Policy and National Adaptation Plan providing detailed roadmaps for policymakers. However, the challenges are increasing, including from slow-moving effects owing to the rising sea level, even as implementation capacity and resource constraints remain significant impediments. The COVID-19 pandemic has amplified those challenges by increasing risks and tightening Grenada's fiscal space.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Grenada